Magnetic glass ceramics by sintering of borosilicate glass and inorganic waste - Ponsot, Ines M. M. M.; Pontikes, Yiannis; Baldi, Giovanni; Chinnam, Rama Krishna Satish; Detsch, Rainer; Boccaccini, Aldo R.; Bernardo, Enrico (Materials, 2014)
Ceramics and glass ceramics based on industrial waste have been widely recognized as competitive products for building applications; however, there is a great potential for such materials with novel functionalities. In this paper, we discuss the development of magnetic sintered glass ceramics based on two iron-rich slags, coming from non-ferrous metallurgy and recycled borosilicate glass. The substantial viscous flow of the glass led to dense products for rapid treatments at relatively low temperatures (900-1000 °C), whereas glass/slag interactions resulted in the formation of magnetite crystals, providing ferrimagnetism. Such behavior could be exploited for applying the obtained glass ceramics as induction heating plates, according to preliminary tests (showing the rapid heating of selected samples, even above 200 °C). The chemical durability and safety of the obtained glass ceramics were assessed by both leaching tests and cytotoxicity tests. © 2014 by the authors.
Keywords: Borosilicate glass; Cytotoxicity tests; Induction heating; Iron-rich slags; Magnetic glass ceramics; Viscous flow sintering